KARAKTERISASI DAN APLIKASI BROMELAIN DALAM PRODUKSI SENYAWA ANTIOKSIDAN ALAMI MELALUI HIDROLISIS PROTEIN DALAM TEPUNG BUNGKIL BIJI NYAMPLUNG (Calophyllum inophyllum L.) - , RATIH RESTIANI; , Dr. Ir. Chusnul Hidayat ([Yogyakarta] : Universitas Gadjah Mada, 2013)
Nyamplung has seeds with a high oil content that makes it potentially used as a raw material for biodiesel. The process of extracting oil from the seeds nyamplung produce waste in the form of oilseed-press cake with protein content of 11.4% that has not been used optimally. One of the alternative process to utilize the cake into valuable products is through enzymatic hydrolysis of nyamplung proteins using bromelain. Bromelain is a group of cysteine endoprotease with broad specificity to cut the amino acid residues arginine, lysine, tyrosine, and phenylalanine, so its application for nyamplung oilseeds protein hydrolysis can produce a high degree of hydrolysis. Utilization of bromelain from pineapple waste has not been much done, and this provides an opportunity to utilize waste as a source of bromelain from core pineapple. This study aimed to: 1) determine the character of the crude bromelain include pH and temperature for optimum activity and stability of crude bromelain, 2) determine the effect of bromelain concentration and hydrolysis time on the DH of the protein hydrolysates and 3) determine the effect of the DH of the antioxidant activity and molecular weight of the protein hydrolysate. The methods of this research consists of four stages : 1) the preparation of nyamplung oilseed press-cake powder , 2) extraction and characterization of crude bromelain from core pineapple, 3) protein hydrolysis using bromelain with variation enzyme concentration and hydrolysis time at pH 7, temperature of 45 0 C for 240 minutes, and 4) analysis of the DH, and the antioxidant activity of protein hydrolysates BM nyamplung seed cake flour. The results showed that the activity of crude bromelain optimum at pH 7 and a temperature of 60 0 C and is stable at pH 7 and temperature (45-50) 0 C. In addition, the increase in the addition of commercial enzymes bromelain and crude bromelain concentration (27,04 and 15,39) U / g substrate produces DH respectively (6,43 and 5,89) %. Time of hydrolysis for 240 min did not show significant changes. Improved DH resulted in increased antioxidant activity of protein hydrolysates nyamplung include % RSA (39,82 and 37,25)%, reducing power (0,382 and 0,359), total phenol content (15,73 and 13,07) mg GAE / g, and molecular weight protein hydrolysate size of 25 kDa, 18 kDa and 8 kDa using SDS-PAGE.